Phylogeny, taxonomy, and zoogeography of the genus Gekko Laurenti, 1768 with the revalidation of G. reevesii Gray, 1831 (Sauria: Gekkonidae) - Rösler, Herbert; Bauer, Aaron M.; Heinicke, Matthew P.; Greenbaum, Eli; Jackman, Todd; Nguyen, Truong Quang; Ziegler, Thomas (Zootaxa, 2011)
A review of the taxonomy, phylogeny, and zoogeography of all currently recognized Gekko species is provided based on morphology (including size, scalation, color, and pattern) and mitochondrial and nuclear DNA sequence data. We distinguish six morphological (phenotypic) species groups within the gekkonid genus Gekko: the G. gecko, G. japonicus, G. monarchus, G. petricolus, G. porosus, and G. vittatus groups, all of which receive support from molecular phylogenetics. The taxon G. reevesii, formerly evaluated as a synonym of G. gekko, is revalidated herein at specific rank. Furthermore, a preliminary identification key of all currently recognized Gekko taxa is provided.